Jumping to conclusions and suicidal behavior in depression and psychosis. (May 2021) - Sastre-Buades, Aina; Ochoa, Susana; Lorente-Rovira, Esther; Barajas, Ana; Grasa, Eva; López-Carrilero, Raquel; Luengo, Ana; Ruiz-Delgado, Isabel; Cid, Jordi; González-Higueras, Fermín; Sánchez-Alonso, Sergio; Baca-García, Enrique; et al.
Abstract: Suicidal behavior (SB) involves an impairment in decision-making (DM). Jumping to conclusions bias (JTC), described as the tendency to make hasty decisions based on insufficient information, could be considered as analogous of impaired DM. However, the link between JTC and SB in psychosis and other diagnoses (e.g., depression) has never been studied. This study aims to explore the presence of JTC and SB in a sample comprising 121 patients with psychosis and 101 with depression. Sociodemographic and clinical data were collected, including history of SB and symptom-severity scores. JTC was assessed by the beads task, and patients who reached decisions with the second bead or before were considered to exhibit JTC. Age, gender, diagnosis, educational level, symptom severity, substance use, and SB were compared according to JTC presence. Variables found to be significantly different in this comparison were included in a multivariate analysis. JTC was more prevalent in patients with depression than with psychosis: 55.6% in an 85:15 ratio and 64.6% in a 60:40 ratio. When multivariate logistic regression was applied to study the influence of diagnosis (psychosis versus depression), age, and SB, only SB remained statistically significant (OR 2.05; 95% CI 0.99–4.22; p = 0.05). The population studied was assembled by grouping different samples from previous research, and we have not included control variables such as other clinical variables, neurocognitive measurements, or personality traits. JTC may be more closely linked to SB, as a transdiagnostic variable, rather than to a specific diagnosis. Highlights: Presence of JTC is higher in depressive and psychotic patients with history of SB, specially under ambiguous conditions. Within individuals who exhibited JTC, more had a diagnosis of depression than psychosis, and that is related to older age. JTC might be considered a transdiagnostic construct present in different psychiatric disorders.